Promoting Excellence and Demonstrated Competence for Nuclear Security Training - Daniel Johnson; Brunelle Battistella; Roger Howsley (International Journal of Nuclear Security, 2016)
The international community has spent considerable time, money, and effort attempting to establish a series of national and regional Centres of Excellence (COEs), also known as Nuclear Security Training and Support Centres (NSSCs). These Centres tend to have a wide variety of objectives, structures, and methods of delivery. Unsurprisingly, no internationally accepted standard exists on how they should operate. The IAEA has produced some excellent guidance (TECDOC 1734), but by virtue of its role cannot provide standards for benchmarking success. Against this backdrop, the World Institute for Nuclear Security (WINS) launched the WINS Academy, an initiative to provide practitioners with opportunities to earn certification in Nuclear Security Management. Underpinning the programme is certification against the ISO 9001 and ISO 29990 quality management standards, which provide an internationally recognised external benchmark of quality; demonstrate credibility, competence and professionalism; and give potential employers and others in the industry an objective measurement of participants’ knowledge. WINS recommends that NSSCs follow a similar model, in which their participants receive an evaluation leading to qualification or certification, and utilizing professional standards developed by a recognised, respected certifying body rather than developing their own ad hoc arrangements, which are ultimately unsustainable. With the end of the Nuclear Security Summit (NSS) process, sustainability is the key consideration for many nuclear security training centres; WINS has sought political and industry commitments to sustain security training programmes, and these efforts were recognised in a Joint Statement on Certified Training for Nuclear Security Management at the 2016 NSS.